The predicament of generation 1.5 English language learners: Three disjunctures and a possible way forward - Schecter, Sandra R. (Canadian Journal of Education/Revue canadienne de l’éducation, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>This article reports key findings from a collaborative project that focused on the academic literacy development of children who are born and/or begin their formal schooling in Canada but are raised in homes where the societally dominant language is not the primary idiom. Analyses involved characterizing students’ home ecological environments; assessing the nature of students’ challenges in relation to school-based literacy demands; and documenting collaborations with professional educators in generating cognitively and pedagogically differentiated instructional approaches. Findings are interpreted as three disjunctive conditions that impede the development of academic literacy competencies and, thus, schooling success of G1.5 linguistic minority students.